Hungary's Cold War : international relations from the end of World War II to the fall of the Soviet Union - Békés, Csaba (New Cold War history., 2022)
"In this magisterial and pathbreaking work, Csaba Békés shares decades of his research to provide a sweeping examination of Hungary's international relations with both the Soviet Bloc and the West from the end of World War II to the dissolution of the Soviet Union in 1991. Unlike many studies of the global Cold War that focus on East-West relationships--often from the vantage point of the West--Békés grounds his work in the East, drawing on little-used, non-English sources"--